The Ticket to Easy Street? The Financial Consequences of Winning the Lottery - Hankins, Scott; Hoekstra, Mark; Skiba, Paige Marta (The Review of Economics and Statistics, 2011)
This paper examines whether giving large cash transfers to financially distressed people causes them to avoid bankruptcy. A comparison of Florida Lottery winners who randomly received $50, 000 to $150, 000 to small winners indicates that such transfers only postpone bankruptcy rather than prevent it, a result inconsistent with the negative shock model of bankruptcy. Furthermore, the large winners who subsequently filed for bankruptcy had similar net assets and unsecured debt as small winners. Thus, our findings suggest that skepticism regarding the long-term impact of cash transfers may be warranted. © 2011 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.